Cryptic diversity in Scorpaenodes xyris (Jordan & Gilbert 1882) (Scorpaeniformes: Scorpaenidae) throughout the tropical Eastern Pacific - Bernal Hernández, Moises Emanuel (2024)
The tropical eastern Pacific (TEP) is a biogeographic region with a substantial set of isolated oceanic islands and mainland shoreline habitat barriers, as well as complex oceanographic dynamics due to major ocean currents, upwelling areas, eddies, and thermal instabilities. These characteristics have shaped spatial patterns of biodiversity between and within species of reef and shore fishes of the region, which has a very high rate of endemism. Scorpaenodes xyris, a small ecologically cryptic reef-dwelling scorpionfish, is widely distributed throughout the TEP, including all the mainland reef areas and all the oceanic islands. This wide distribution and its ecological characteristics make this species a good model to study the evolutionary history of this type of reef fish across the breadth of a tropical biogeographical region. Our evaluation of geographic patterns of genetic (mitochondrial and nuclear) variation shows that S. xyris comprises two highly differentiated clades (A and B), one of which contains four independent evolutionary subunits. Clade A includes four sub-clades: 1. The Cortez mainland Province; 2. The Revillagigedo Islands; 3. Clipperton Atoll; and 4. The Galapagos Islands. Clade B, in contrast, comprises a single unit that includes the Mexican and Panamic mainland provinces, plus Cocos Island. This geographical arrangement largely corresponds to previously indicated regionalization of the TEP. Oceanic distances isolating the islands have produced much of that evolutionary pattern, although oceanographic processes likely have also contributed.